Faktor Ibu Dan Anak Pada Kejadian Stunting Di Puskesmas Batakte - Amelya Sir; Simplexius Asa; Indriati Tedjuhinga; Imelda Manurung; Dwi Windoe; Ampera Wadu (Jurnal Kesehatan, 2022)
Stunting toddlers have a risk of decreased intellectual ability, productivity, and an increase in degenerative diseases in the future. The results of the 2018 Riskesdas show that East Nusa Tenggara Province is the province with the highest proportion of of short and very short nutritional status of children under five, which is 42.4%. The purpose of the study was to analyze the risk factors for stunting in children under five in the working area of the Batakte Health Center. The research design was a case-control study. The research subjects were toddlers aged with the case group being stunted toddlers while the control sample was normal toddlers with a ratio of 1:1 as many as 48 toddlers and mothers of toddlers as respondents. Data analysis used the chi-square test and OR calculation to assess risk factors. The research was conducted in the working area of the Batakte Health Center from August-October 2021. Research variabels are history of infectious disease, low birth weight, maternal education, parenting style,maternal occupation age at pregnancy and gestational age. The results showed that there was a relationship between a history of infectious disease (OR=5,000; 95% CI 1,165-21,459), low birth weight (LBW) (OR=5,909; 95% CI 1,546-22.580), maternal education (OR=4,491; 95% CI 1,260-16,006) and parenting style (OR= 6,000; 95% CI 1,711-21,038) with stunting in children under five, while maternal occupation, age at pregnancy and gestational age were not associated with stunting in children under five in the region Batakte Health Center